HOW ARTIFICIAL INTELLIGENCE TRANSFORMS THE WORK OF PROJECT MANAGERS IN THE U.S. MARKET - Chekhla, Serhii (Global Prosperity, 2026)
This article examines how artificial intelligence (AI) transforms the work of project managers in the contemporary U.S. market. The study analyzes the impact of AI on the core functions of project management, including planning, coordination, communication, reporting, risk management, decision-making, stakeholder interaction, and team collaboration. Special attention is given to the redistribution of responsibilities between human project managers and AI systems, as well as to the growing importance of digital literacy, analytical thinking, ethical judgment, and AI-assisted decision-making competencies. The article argues that AI does not eliminate the need for project managers, but fundamentally changes the structure of their work. Routine, repetitive, and data-intensive tasks are increasingly automated, while the human role shifts toward leadership, strategic thinking, communication, insight interpretation, and supervision of AI-supported processes. The study also considers how AI changes the speed of communication, the transparency of project execution, and the quality of decision-making in complex project environments. A separate focus is placed on the evolution of the project manager's competency model, including AI literacy, critical thinking, data interpretation, adaptability, and human-centered leadership. The research also highlights ethical and governance-related issues associated with AI adoption, such as accountability, algorithmic bias, transparency, privacy, and the risks of over-reliance on automation. In addition, the paper examines barriers to AI adoption in project environments, including skill gaps, resistance to change, fragmented systems, and unrealistic expectations regarding automation. The practical significance of the study lies in its applicability for organizations, PMOs, educators, and project professionals seeking to understand how the profession of project manager evolves under the influence of AI and which competencies will remain essential in the coming years.